Surgical Removal of Embolized Ventricular Septal Occluder Device. (July 2017) - Vaidhya, Nikunj; Mishra, Amit; Siddiqui, Sumbul; Joshi, Harshil; Patel, Hardik
Ventricular septal defect (VSD) with valvar pulmonary stenosis (PS) is a combination of cardiac defects for which treatment by means of percutaneous catheter-directed intervention is sometimes considered. Septal occluder device embolization is a rare but potentially dreadful complication. Adequate precautions are of great importance, as operator-related and anatomical factors can contribute to the risk of device embolization. In this report, we present a case of a five-year-old patient with a perimembranous VSD and valvar PS with infundibular muscle hypertrophy. The PS was treated with balloon pulmonary valvotomy, and the VSD was closed with a catheter-directed duct occluder device. Soon after deployment, the device embolized to the aortic arch, possibly as a result of the single disc device being "milked" out of VSD by dynamic contractions of hypertrophied muscle in the right ventricular outflow tract. The embolized device was successfully retrieved and removed using cardiopulmonary bypass and a period of circulatory arrest.